A STUDY OF BUYING BEHAVIOUR OF RURAL CONSUMERS - Tripathi, Prashant (Innovative Research Thoughts, 2017)
Consumer behaviour is described as the process of selecting, buying, using and disposing goods and services by individuals or organisations to satisfy their wants. Companies have to understand the various factors that influence consumers to make purchases these factors may be reference groups, cultural factors, and economic factors and alike, they also need to understand the purchase process that goes into making purchase decisions by consumers in order to succeed in both rural and urban markets. The rural markets provide a wide array of opportunities due to their vast size and changes that have taken place over the years. In recent years, rural markets have acquired significance, as the overall growth of the economy has resulted into substantial increase in the purchasing power of the rural communities. Rural Markets are defined as those segments of overall market of any economy, which are distinct from the other types of markets like stock market, commodity markets or Labour economics. In this present study, the buying behaviour of rural consumers is studied. Factors affecting the buying decision of the rural consumers are also considered in the study.